Protocol for quality control in radioguided surgery procedures for detection and removal of sentinel node and non palpable lesions (Revista de Física Médica, 2015)
In this work the process for the detection and/or removal of the sentinel lymph node and nonpalpable lesions has been optimized. For the latter, a I-125, seed an isotope that is not usually used for this purpose, is employed. It was recycled from radiotherapy treatments surpluses, having requested the necessary authorizations. A detailed procedure for the management, storage, transport and sterilization of the I-125 seed in the hospital has been developed. A custom protocol has been defined for quality control of intraoperative probes with different tests, providing methods, frequencies, tolerances, etc. The overall result is an improvement of the process and a decrease of the inconveniences for the patient.